PENGARUH INFLASI, NILAI TUKAR KURS, SUKU BUNGA SBI TERHADAP HARGA SAHAM - Toto Raharjo; Nurdianingsih, Indah Eka Putri Pramesti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The purpose of this research is to identify the effect of inflation, USD’s exchange rate, and SBIinterest rate on stock prices. Using purposive sampling, nine companies listed on the IndonesiaStock Exchange from 2017 to 2021 were selected as the sample. The independent variables areinflation, USD’s exchange rate, and SBI interest rate, and the dependent variable is stock prices. The multiple linear regression analysis performed in this study has led to findings that inflation and USD’s exchange rate significantly affect stock prices and that SBI interest rate does not influence the stock prices.